2015
DOI: 10.3389/fnhum.2015.00139
|View full text |Cite
|
Sign up to set email alerts
|

A real-life illusion of assimilation in the human face: eye size illusion caused by eyebrows and eye shadow

Abstract: Does an assimilative illusion like the Delboeuf illusion occur in the human face? We investigated factors that might influence the perceived size of the eyes in a realistic face. Experiment 1 manipulated the position of the eyebrows (high or low), the presence/absence of eye shadow, and the viewing distance (0.6 m or 5 m), then measured the perceived eye size using a psychophysical method. The results showed that low eyebrows (i.e., closer to the eyes) make the eyes appear larger, suggesting that the assimilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 25 publications
7
38
0
Order By: Relevance
“…We predicted that the eyes and mouth would look larger with makeup. Indeed, the eyes were perceived as larger with makeup than without across all three studies, corroborating recent work by Morikawa et al (2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We predicted that the eyes and mouth would look larger with makeup. Indeed, the eyes were perceived as larger with makeup than without across all three studies, corroborating recent work by Morikawa et al (2015).…”
Section: Discussionsupporting
confidence: 89%
“…Despite the widely held belief that makeup makes the eyes and lips look larger, the idea has received almost no scientific evaluation. Recently, Morikawa and colleagues used psychophysical methods to test whether the eyes appear larger when wearing eyeshadow (Morikawa, Matsushita, Tomita, & Yamanami, 2015). They found that faces wearing eyeshadow appear to have larger eyes, and that the effect is moderated by the distance between the eyes and the eyebrows, as well as by the viewing distance from the face.…”
mentioning
confidence: 99%
“…Aspects of facial contrast are sexually dimorphic, being greater in female than male faces (Jones et al ., ; Russell, ; Russell, Kramer, & Jones, ), while other aspects decline with age and are used as cues for perceiving age and health from the face (Porcheron, Mauger, & Russell, ; Porcheron et al ., ; Russell et al ., , ). Theorists have proposed that facial feature size mediates the effect of makeup on attractiveness (Bruce & Young, ; Morris, , ; Perrett, ; Zebrowitz, ), and recent work has shown that makeup does indeed make the eyes and eyebrows appear larger (Morikawa, Matsushita, Tomita, & Yamanami, ). Makeup can also make the nose appear smaller, through the use of contouring, but typically does not make the lips appear any larger (Jones, Porcheron, & Russell, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the eye size illusion is also induced by the distance between the eyebrow and eye and may involve a different type of assimilation illusion. 24 The shortened distance between the eyebrow and eye is reported to increase the illusion of a larger eye. 25 Hence, the visually perceived dimension and aesthetics of the eye are further influenced by the relative proportions of the eyebrow–eye anatomical unit.…”
Section: Discussionmentioning
confidence: 99%